(untitled) (Research, Society and Development, 2021)
Long term vesical bladder technique demands a huge scientific-technical knowledge from those who perform it. An educational video may be an educational technology for developing skills and abilities for using this technique. This article aims to describe the process of developing an educational video about female and male long-term vesical bladder. It is a descriptive study in order to show the steps applied along the elaboration of an educational video Nurse Undergraduate students from a public university took part in it. There were three important stages along the development process: the pre-production which involves the search of the contents, the script and management; the production which means building the set, choosing the characters and recording it; and the post production in which the images were edited and titles and images included. There must be highlighted the students participation once being taking part in this process they have learned by doing it. This educational video showed to be efficient in its constitution since it is an educational technology for health teaching-learning process.